Seedling regeneration, environment and management in a semi-deciduous African tropical rain forest - Mwavu, Edward N.; Witkowski, Edward T.F. (Journal of Vegetation science, 2009)
How is seedling regeneration of woody species of semi-deciduous rain forests affected by (a) historical management for combinations of logging, arboricide treatment or no treatment, (b) forest community type and (c) environmental gradients of topography, light and soil nutrients? Location: Budongo Forest Reserve, Uganda. Methods: Seedling regeneration patterns of trees and shrubs in relation to environmental factors and historical management types were studied using 32 0.5-ha plots laid out in transects along a topographic gradient. We compared seedling species diversity, composition and distribution patterns along topographic gradients and within types of historical management regimes and forest communities to test whether environmental factors contributed to differences in species composition of seedlings. Results: A total of 85 624 woody seedlings representing 237 species and 46 families were recorded in this rain forest. Cynometra alexandri C.H. Wright and Lasiodiscus mildbraedii Engl. had high seedling densities and were widely distributed throughout the plots. The most speciesrich families were Euphorbiaceae, Fabaceae, Rubiaceae, Meliaceae, Moraceae and Rutaceae. Only total seedling density was significantly different between sites with different historical management, with densities highest in logged, intermediate in logged/arboricided and lowest in the nature reserve. Forest communities differed significantly in terms of seedling diversity and density. Seedling composition differed significantly between transects and forest communities, but not between topographic positions or historical management types. Both Chao-Jaccard and Chao-S rensen abundance-based similarity estimators were relatively high in the plot, forest community and in terms of historical management levels, corroborating the lack of significant differences in species richness within these groups. The measured environmental variables explained 59.4% of variance in seedling species distributions, with the three most important being soil organic matter, total soil titanium and leaf area index (LAI). Total seedling density was positively correlated with LAI. Differences in diversity of 42.0 cm dbh plants (juveniles and adults) also explained variations in seedling species diversity. Conclusions: The seedling bank is the major route for regeneration in this semi-deciduous tropical rain forest, with the wide distribution of many species suggesting that these species regenerate continuously. Seedling diversity, density and distribution are largely a function of adult diversity, historical management type and environmental gradients in factors such as soil nutrient content and LAI. The species richness of seedlings was higher in soils both rich in titanium and with low exchangeable cations, as well as in logged areas that were more open and had a low LAI.
Keywords: Albertine rift ecoregion; Analysis of similarity; Chao’s Similarity estimators; Continuous regeneration; Ecological resilience; Leaf area index